Edukasi peran fisioterapi dalam pencegahan diabetes mellitus melalui latihan fisik - Maulana Ahsan Fadhail; Akmil Angfasa Ridho; Anwaar Isnaenuddin (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Diabetes mellitus (DM) is a non-communicable disease with a steadily rising prevalence; Indonesia ranks fifth globally, with an estimated 20.4 million people living with DM in 2024. Bandar Lampung City is recorded as having one of the highest burdens of DM cases in Lampung Province; however, public knowledge regarding DM prevention and management specifically concerning the roles of physiotherapy and physical exercise remains low. Purpose: To enhance public knowledge regarding the role of physiotherapy in DM prevention and management through education on physical exercise. Method: This community service activity was conducted at the At-Taubah Mosque (Perum BKP Block S, LK III, Bandar Lampung City) on June 12, 2026. The initiative aimed to inform the community about DM and the role of physiotherapy in its management and prevention. Thirty women from a local religious study group participated in the activity. Respondent knowledge and understanding were assessed using a one-group pretest-posttest design, utilizing questionnaires administered before (pretest) and after (posttest) the educational session. Data were analyzed descriptively and tested using simple statistics (paired t-test) to determine the significance of changes in knowledge scores and to illustrate the distribution of knowledge levels before and after the activity. An observational evaluation was also conducted to assess the activity's outcomes, involving guidance provided to participants during practical simulations of physiotherapy techniques. Results: The mean age of participants was 45.8 years, with the majority (n=22; 73.3%) falling within the 40–50 age range. Most participants had a high school education (n=19; 63.3%), and the majority were housewives (n=24; 80.0%). Regarding knowledge levels prior to the educational activity, 3 participants (10.0%) were in the